Spending responses to state sales tax holidays - Sumit Agarwal; Leslie McGranahan (Federal Reserve Bank of Chicago, 2012)
Every year over 20 states offer sales tax holidays (STHs) on specific items like clothes, shoes and other items to encourage consumption, effecting over 100 million consumers. We use a unique dataset of credit cards transaction to study the spending response to these holidays. Using a diff-in-diff methodology, we find that STHs increase overall daily spending by 8%, with large percentage increases in spending on children's clothes and shoes of 193% and 98% respectively. Consumers with children increase spending more during STHs. Our estimates of price elasticities range from 6 for big box merchants to 30 for kids clothing merchants (in absolute terms). There is no evidence of inter-temporal substitution either before or after the STH or cross-product substitution away from non-treated goods. Finally, we show that consumers from across state borders also take advantage of these tax holidays and shop in states offering holidays. Our falsification tests rule out concerns that our results are driven by spurious correlations.
Keywords: D12; G21; H20; H71; L81; 330; Consumption; State Sales Tax Holidays; Back to School; Credit Cards; Household Finance; Banks; Loans; Shopping; Spending